Dedication (Cambridge quarterly of healthcare ethics, 2002)
This issue of the journal had already been planned when CQ lost its own “first voice,” David Thomasma. David died unexpectedly on April 25, 2002, after undergoing surgery. The Special Section herein titled “First Voices,” with collected reminiscences of some early bioethics pioneers, had been David's idea from beginning to end. As such, we had decided to deviate from our usual practice of a collaborative editorial and to have David offer a solo voice from the perspective of someone who intimately participated in molding the discipline. This issue of CQ, which we dedicate to him, was his last project.